Sepa Api dalam Ritual Katodo Ngagha pada Etnik Pautola Keo Tengah Flores: Sebuah Kajian Semiotik - Tao, Kristina Maria B; Genua, Veronika (Program Studi Pendidika Bahasa dan Sastra Indonesia, 2021)
This study aims to describe the Sepa Api symbol in the Katodo Ngagha Traditional Ritual of the Patola ethnic, Keo Tengah, Flores. Sepa Api semiotics describes the symbols and meanings contained in Sepa Api. The problems in this study are (1) What are the shapes of the sepa fire symbols in the Katodo Ngagha ritual for the Patola, Central Keo, Flores ethnics (2) How are the fire sepa symbols in the Katodo Ngagha ritual for the Patola, Central Keo, Flores ethnicities. 1) To find and describe the fire sepa in the Katodo Ngagha ritual for the Patola ethnic, Keo Tengah, Flores (2) to find and describe the meaning of the fire sepa in the Katodo Ngagha ritual for the Patola ethnic, Keo Tengah, Flores. The approach used in this study is a qualitative descriptive approach. The data were collected using the proficient method, the listening method, and the recording method while the techniques used were interview techniques, note-taking techniques, and documentation techniques. The theory used in this study is the theory of Semiotics. The results of the analysis show that there is a form of the fire sepa symbol in the Katodo Ngagha Ritual of the Patola ethnic, Keo Tengah, Flores which has seven (7) forms and four (4) meanings. Seven (7) semiotic forms of sepa api, namely: (1) sepa api, (2) kae yeast and dambu bhala, (3) poji tolo, (4) lipe, (5) wonda, (6) topo, (7) nggo and longing. The meanings of the symbols or symbols on the fire sepa are: (1) religious meanings, (2) social meanings, (3) power meanings, (4) entertainment meanings.